Unequal treatment in pretrial detention in China - Xiong, Moulin (The British journal of criminology, 2017)
Drawing on 4,098 documents concerning adjudication decisions from three district courts in China, this study reveals that white-collar offenders enjoy favourable treatment in pretrial detention. Using statistical analysis, the article reveals that suspects without resources and social status are significantly more likely to be detained before trial; the higher rates of self-surrender and good behaviour among white-collar offenders play a vital role in considerably lowering the possibility of detention; bailed white-collar offenders also have advantages over detained suspects in probation and sentencing outcomes. Unlike previous studies on the extralegal reasons as explanations for these findings, we expand our perspectives to include the law, shuanggui, flaws in evidence, resources, crime-control orientation policy and punitive culture in order to explain the disparities.